Information on The Distribution Of Blood Donors Using GIS In Jayapura City (Case Study: UTD PMI Jayapura City) - Nanda Rizky; Elvis Pawan; Jim Lahallo (Institut Teknologi Bisnis AAS Indonesia, 2023)
The existence of UTD PMI Jayapura City is very helpful for the surrounding community in terms of health. People can also donate blood through the PMI clinic and get blood donors. Donors often have to queue to get their turn to register if they will donate blood at a blood donation event due to constraints in the health service process which is still carried out conventionally, namely by direct recording of potential donors. In addition, the absence of a computerized system to provide information regarding donor data remains a major problem, hampering blood donation services at PMI. The current system cannot produce clear and accurate data to help people assist. Quickly in case of an emergency. The PIECES method is used for reference in building several features in the system by conducting information, economic, security, efficiency, and service performance analysis to find weaknesses in the current system and offer suggestions for improvements to be made on newly built systems and using GIS as it can assist in the presentation of more interactive map information. The expected result of this research is to produce a system that can map the location of donors who have been divided based on their blood type so that the search process will be more efficient and can help search activities at PMI. Donor mapping in this system is also equipped with complete data from donors so that officers can find out the location of donors and can contact donors through existing data